Design of bespoke lightweight cement mortars containing waste expanded polystyrene by experimental statistical methods. (5th January 2016) - Ferrándiz-Mas, V.; Sarabia, L.A.; Ortiz, M.C.; Cheeseman, C.R.; García-Alcocel, E.
Abstract: This work assesses the reuse of waste expanded polystyrene (EPS) to obtain lightweight cement mortars. The factors and interactions which affect the properties of these mortars were studied by ad-hoc designs based on the d-optimal criterion. This method allows multiple factors to be modified simultaneously, which reduces the number of experiments compared with classical design. Four factors were studied at several levels: EPS type (two levels), EPS content (two levels), admixtures mix (three levels) and cement type (three levels). Two types of aggregate were also studied. The workability, air content, compressive strength, adhesive strength, bulk density and capillary absorption were experimentally tested. The effect of factors and interactions on the properties was modelled and analysed. The results demonstrate how the factors and synergistic interactions can be manipulated to manufacture lightweight mortars which satisfy the relevant EU standards. These mortars contain up to 60% of waste EPS, low amounts of admixtures and low clinker content CEM III. Sustainable mortars containing silica sand gave flow table spread values between 168 and 180 ± 4 mm, bulk density between 1280 and 1110 ± 100 kg/m 3, and C90 between 0.279 and 0.025 ± 0.07 kg/m 2 ·min 0.5, making them suitable for masonry, plastering and rendering applications. Graphical abstract: Highlights: D-optimal criterion reduced the experiments needed to design lightweight mortars. Workability increased by using ground waste expanded polystyrene (EPS). EPS content had no significant impact on compressive strength of limestone mortars. Ground EPS mortars had lower C90 than powdered EPS mortars, thus better durability.